2019
DOI: 10.1177/0954406219833722
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analyses of wedge effects on the rooster tail and porpoising phenomenon of a high-speed planing craft in calm water

Abstract: This paper presents experimental and numerical investigation of stability and rooster tail of a mono-hull high-speed planing craft with a constant deadrise angle. Initially, a one-fifth scale model was tested in a towing tank, which showed porpoising phenomenon at 8 m/s (equal to the speed of sailing). Subsequently, two wedges of 5 and 10 mm heights, based on the boundary layer calculations, were mounted on the aft section of the planing hull. These wedges were shown to increase the lift at the aft section. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Wedge efects were frst studied by Ghadimi et al [9] in an experimental manner, considering two stern wedges with diferent heights. After that, the rooster tail of wedgemounted hulls was analyzed in a more comprehensive study via both experimental and numerical methods by Mahdi Sajedi et al [31]. Te seakeeping of wedgemounted hulls in irregular waves was also studied experimentally by Ghadimi et al [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wedge efects were frst studied by Ghadimi et al [9] in an experimental manner, considering two stern wedges with diferent heights. After that, the rooster tail of wedgemounted hulls was analyzed in a more comprehensive study via both experimental and numerical methods by Mahdi Sajedi et al [31]. Te seakeeping of wedgemounted hulls in irregular waves was also studied experimentally by Ghadimi et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…Tey found that the simultaneous use of stern wedges and transverse steps could improve the vessel's undesirable performance prior to planing regime, which is one of the challenges in planing hull design. Tese extensive data [9,28,29,[31][32][33][34][35][36][37] for diferent confgurations of a single parent model present a unique opportunity to realize how diferent confgurations of step and wedge could afect a planing hull's performance.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that the wedge effects on the same parent model have been assessed experimentally 9,15 and numerically. 16…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, some researchers verified and optimized numerical model through the comparison with model tests, and then the verified model can be used for further analysis and research. 16,20,21…”
Section: Introductionmentioning
confidence: 99%